2016
DOI: 10.17755/esosder.21699
|View full text |Cite
|
Sign up to set email alerts
|

Matemati̇k Öğretmen Adaylarinin Alan Ve Alan Eği̇ti̇mi̇ Dersleri̇ne Yöneli̇k Tutumlari: Karma Bi̇r Araştirma

Abstract: ÖzBu araştırmanın amacı, ortaöğretim matematik öğretmen adaylarının alan ve alan eğitimi derslerine yönelik tutumlarını belirlemek ve cinsiyet, sınıf gibi değişkenlere göre incelemektir.Bu araştırma, nicel ve nitel araştırma yöntemlerinin bir arada kullanıldığı karma bir araştırma yöntemi ile yürütülmüştür. Araştırmaya ortaöğretim matematik öğretmenliği programına devam eden 110 öğretmen adayı katılmıştır. Veri toplama araçları olarak alan ve alan eğitimi derslerine yönelik tutum ölçekleri ve görüşme formu kul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
4
1
1
Order By: Relevance
“…In their study, Bukova-Güzel, Elçi and Alkan (2006) emphasize the necessity of attaching required importance to mathematics education without putting the mathematics knowledge aside in teacher training. This contradicts with the study of Özgen and Obay (2016), in which they found a low level of relationship between them.…”
Section: Suggestionscontrasting
confidence: 84%
See 2 more Smart Citations
“…In their study, Bukova-Güzel, Elçi and Alkan (2006) emphasize the necessity of attaching required importance to mathematics education without putting the mathematics knowledge aside in teacher training. This contradicts with the study of Özgen and Obay (2016), in which they found a low level of relationship between them.…”
Section: Suggestionscontrasting
confidence: 84%
“…However, it can be said that the prospective teachers' final attitudes toward the mathematics education courses were slightly higher than their attitudes toward the mathematics courses. As a result of their study, Özgen and Obay (2016) determined that the mean attitude scores of the prospective teachers in relation to the mathematics courses and the mathematics education courses were at similar level. In the study made by Turanlı et al (2007), it was obtained that the prospective teachers had positive attitudes toward the mathematics courses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, reported that university teaching staff at PE and sports education department have positive attitudes toward technology and majority of them found the technological equipment in their schools to be insufficient and they didn't attend any course related to technology. Obay and Özgen (2008), determined in their study where they investigated the attitudes of candidate teachers towards education technologies that the variable of getting the lecture of teaching technologies and material development affected positively the attitudes of candidate teachers towards education technologies. Yılmaz et al (2010) stated in their study on the determination of the attitudes and opinions of students at PET program towards the use of technology in education that students' use of technological materials in teaching affect positively the attitude scores of students.…”
Section: Resultsmentioning
confidence: 99%
“…With these methods, they state that PTs will not be able to gain proficiency in how they will transfer the topics they learned in their major area courses into their lives. Özgen and Obay (2016) stated that PTs have problems about how they relate mathematics to pedagogy. Teaching that is regardless of the relation between the major area courses with the professions of PTs can be effective on the base of these problems.…”
Section: Discussion Of the Findings Related To The Conduct Of The Courses In Elementary Mathematics Teaching Programsmentioning
confidence: 99%